Development of biosensors based on hexacyanoferrates - de Mattos, I. L.; Gorton, L.; Laurell, T.; Malinauskas, A.; Karyakin, A. A. (Elsevier B.V., 2000)
Ferric and copper hexacyanoferrates (PB and CuHCF, respectively) were electrodeposited on glassy carbon electrodes providing a suitable catalytic surface for the amperometric detection of hydrogen peroxide. Additionally glucose oxidase was immobilized on top of these electrodes to form glucose biosensors. The biosensors were made by casting glucose oxidase-Nafion layers onto the surface of the modified electrodes. The operational stability of the films and the biosensors were evaluated by injecting a standard solution (5 mu M H2O2 for PB, 5 mM H2O2 for CuHCF and 1.5 mM glucose for both) over 5-10 h in a now-injection system with the electrodes polarized at - 50 (PB) and -200 mV (CuHCF) versus Ag/AgCl, respectively. The glucose biosensors demonstrated suitability for glucose determination: 0.0-2.5 mM (R-2 = 0.9977) for PB and 0.0-10 mM (R-2 = 0.9927) for CuHCF, respectively. The visualization of the redox catalyst modifiers (PB and CuHCF films) was presented by scanning electron micrographs. (C) 2000 Elsevier B.V. B.V. All rights reserved.
Keywords: Prussian Blue; copper hexacyanoferrate; hydrogen peroxide; biosensor